2023
DOI: 10.1002/jcp.31126
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity attenuates skin wound healing by inhibiting dermal fibroblast migration via F‐actin/YAP signaling pathway

Yuhao Zhou,
Wenjun Lv,
Xiufen Peng
et al.

Abstract: Skin and its cell components continuously subject to extrinsic and intrinsic mechanical forces and are mechanical sensitive. Disturbed mechanical homeostasis may lead to changes in skin functions. Gravity is the integral mechanical force on the earth, however, how gravity contributes to the maintenance of skin function and how microgravity in space affects the wound healing are poorly understood. Here, using microgravity analogs, we show that simulated microgravity (SMG) inhibits the healing of cutaneous wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Yang and colleagues (2016) showed that SMG could alter the circadian rhythm of 3T3 cells by influencing the mRNA expression of circadian genes and induce a change in Per1 and Per2 expression [19]. Fibroblasts exhibit high sensitivity to SMG, which validates the possible significance of the TGF-β1/Smad3 signaling pathway in regulating wound healing [20]. A recent study revealed that changes in fibroblast structures and delayed cell migration were the main effects of altered gravity, contributing to alterations in the fibroblasts' function related to wound healing [21].…”
Section: Discussionmentioning
confidence: 98%
“…Yang and colleagues (2016) showed that SMG could alter the circadian rhythm of 3T3 cells by influencing the mRNA expression of circadian genes and induce a change in Per1 and Per2 expression [19]. Fibroblasts exhibit high sensitivity to SMG, which validates the possible significance of the TGF-β1/Smad3 signaling pathway in regulating wound healing [20]. A recent study revealed that changes in fibroblast structures and delayed cell migration were the main effects of altered gravity, contributing to alterations in the fibroblasts' function related to wound healing [21].…”
Section: Discussionmentioning
confidence: 98%
“…So far, multiple changes occurring in tissues and on the cellular level have been reported [30,31]. Human cell cultures of benign and malignant cells exposed to real microgravity (r-µg, also called weightlessness) in space showed several morphological and molecular changes [32][33][34][35][36][37][38][39][40][41]. Low differentiated FTC-133 follicular thyroid cancer cells studied in space for 10 days (d) during the Shenzhou-8 space mission showed changes in growth behavior and exhibited two different phenotypes after spaceflight.…”
Section: Introductionmentioning
confidence: 99%